Motor Development of Children in the Kurdistan Region of Iraq: Parent Survey - Francesca Policastro; Nizar Bakir Yahya; Alessandra Rossi; Giorgia Silli; Giovanni Galeoto; Nezar Ismet Taib (MDPI AG, 2024)
The actual literature highlights the importance of the socio-cultural context in the development of children. However, there is a lack of specific evidence about the middle East, especially regarding the development of Kurdish children who are living in a post-war scenario, in a country which is experiencing continuous instability due to the different crises. The main aim of this study is to identify the features of the motor development of Kurdish children according to parents' opinion. A comparison with Italian children is provided as a Western example, which reflects data from the literature. In the study, 331 parents of Kurdish and Italian children aged between 3 and 7 years were involved. Parents filled the questionnaire at kindergartens, after providing consent. The questionnaire was conceptualized, designed, tested and provided ad hoc for this study; it focused on the timing of development, concerning major milestones like head control, sitting and standing-up. The questionnaire consists of 15 questions and has not been standardized yet. A logistic regression showed several differences between Kurdish and Italian children, like head control (p = 0.007) or the manipulation of big objects (p < 0.0001). These results identify the effect of the socio-cultural context and the impact of the growing environment of the child. Moreover, the results of this survey show the need for introducing different adapted, translated and validated assessment tools for motor development, considering differences related to the socio-cultural context.